A simulation of single stage BJT amplifier using LTSpice / Mohammad Nizam Ibrahim ... [et al.] - Ibrahim, Mohammad Nizam; Che Soh, Zainal Hisham; Hamzah, Irni Hamiza; Othman, Ali (2016)
Students and academicians at universities around the world use a variety of simulation tools to measure important characteristics of electrical and electronic circuits. Most students, however, cannot afford to own the simulation tools because those can be very expensive. Without having any simulation tools, a learning process can be hindered since the students are required to complete a number of homeworks, assignments, and pre-laboratory tasks outside their classrooms. This paper presents a popular and free of charge simulation tool for electrical and electronic circuits known as LTSpice. To demonstrate the capability of the tool, a basic single stage common emitter Bipolar Junction Transistor (BJT) amplifier is constructed and simulated by using the LTSpice. There are four important characteristics of the amplifier: emitter current, voltage gain, input impedance, and output impedance are measured and then compared with theoretically calculation. The comparison results show a high accuracy is achieved for all the amplifier characteristics. The measured emitter current and output impedance achieved 100% accuracy while the voltage gain and input impedance achieved 99.1% and 99.7% accuracy, respectively. Therefore, this paper provides an encouragement for the students and academicians to own and use the LTSpice simulation tool to simulate electrical and electronic circuits in their learning and teaching processes.